2006
DOI: 10.1002/anie.200503280
|View full text |Cite
|
Sign up to set email alerts
|

Control of Stereoselectivity in an Enzymatic Reaction by Backdoor Access

Abstract: The ability of biopolymers to discriminate between optical isomers is vital for living systems, and the selective formation of only one product stereoisomer from achiral substrates is one of the most sophisticated tasks for enzymes. Using a Diels-Alder ribozyme as an example, we demonstrate here that by a simple strategy a biocatalyst can be used to selectively synthesize both product stereoisomers in one catalytic pocket, namely, by controlling access to the active site from opposite directions through differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…To enter the pocket in this orientation, it must have squeezed through an opening that is, according to the X-ray structure, far too narrow (9). (2) It was recently demonstrated that, under certain conditions, the anthracene diene can enter the pocket from the ‘wrong’ side, through a small ‘back door’ opening, giving rise to an alternative stereochemical course of the reaction (44). Again, the dimensions of this orifice are too small for the substrate to gain access.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…To enter the pocket in this orientation, it must have squeezed through an opening that is, according to the X-ray structure, far too narrow (9). (2) It was recently demonstrated that, under certain conditions, the anthracene diene can enter the pocket from the ‘wrong’ side, through a small ‘back door’ opening, giving rise to an alternative stereochemical course of the reaction (44). Again, the dimensions of this orifice are too small for the substrate to gain access.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Jäschke and coworkers have extensively studied a ribozyme that was identified for the Diels-Alder reaction between anthracene and maleimide substrates. [25,57] Primarily for comparison purposes, identification of deoxyribozymes for the Diels-Alder reaction was undertaken by Chandra and Silverman. [27] The RNA sequence of Jäschke's 39M49 ribozyme was partially randomized and prepared as DNA.…”
Section: Dna As a Catalystmentioning
confidence: 99%
“…[27] The sense of enantioselectivity is not known, although there is an appreciable degree of enantioselectivity (M. Chandra and S.K.S., unpublished data), as is the case for Jäschke's Diels-Alder ribozyme. [25,57] …”
Section: Figurementioning
confidence: 99%
“…The ( R , R )‐enantiomer of the product has been concluded to be more favorable by 16% of enantiomeric excess based on chemical studies. [15, 16] [Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com.]…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently found that the Diels‐Alderase ribozyme can be used to selectively synthesize both product enantiomers in one catalytic pocket by controlling access to the active site from opposite directions through different “doors”. [16] Indeed, the X‐ray crystal structure of the ribozyme:product complex revealed that the catalytic center is accessible from both “front” and “back” doors, involving openings of different sizes. [19] For the purpose of crystallization, the reaction was performed with the diene substrate covalently linked to the ribozyme by a short flexible tether, yielding a reaction product bound as the ( S , S )‐enantiomer (over 90% of enantiomeric excess), whereas the untethered catalytic reaction produces predominately the ( R , R )‐enantiomer (16% of enantiomeric excess),[15, 16] see Figure 1.…”
Section: Introductionmentioning
confidence: 99%